Preliminary reflections on LGBTQIA+ com-munity and queer theory in informational studies - Mosso, Erick Faria (2022)
The study developed is based on a research prob-lem that is located in the need to invest and deep-en research related to the LGBTQIA+ community, in the scope of Librarianship and Information Science (BCI). It is assumed that, although growing, the number of scientific production on the subject is still insipient, given the Brazilian social configuration in relation to the proportionality of this community in the country. More specifically, he considers that Judith Butler's Queer Theory could serve as a basis for the construction of a discussion matrix for informational studies, in order to encourage the area to build concepts, theories and methodologies for informational studies that are coherent with the demands of this community. In order to verify the indicated assumptions, the specific objectives of this research were to present briefly the context of Queer Theory and to verify the quantification of scientific production on subjects related to LGBTQIA+ themes, initially in international data-bases in ICB, and then in national databases of the area. At the end, we aimed to build a general analysis of how scientific works on the subject are being produced. As a methodological contribution, an exploratory research was developed, based on a bibliographic and documental survey. The international databases listed were: Information Science & Technology Abstracts Library, Information Science & Technology Abstracts with Full Tex; Library and Information Science Abstracts. The national databases were BRAPCI, RPPBCI and the FEBAB Repository. The resource used to analyze the bibliographical and documental productions was content analysis. At the end of the argumentative process built, the analysis is made on how the elements presented in the scope of Queer Theory can contribute to a critical reflection in the scope of CI and Knowledge Organization (KO).